Adequacy of Nutrient Intakes of Severely and Acutely Malnourished Children Treated with Different Doses of Ready-To-Use Therapeutic Food in Burkina Faso - Nikièma, Victor; Kangas, Suvi T.; Salpéteur, Cécile; OUEDRAOGO, Abdoulaye; Lachat, Carl; BASSOLE, Nestor H. I.; Nadia, Fanou (My University, 2021)
Ready-to-use therapeutic foods (RUTF) are designed to cover the daily nutrient requirements of children with severe acute malnutrition (SAM). However, with the transfer of uncomplicated SAM care from the hospital environment to the community level, children will be able to consume complementary and family foods (CFF) in addition to RUTF, and this might decrease the quantity of RUTF needed for recovery. Using an individually randomized clinical trial, we investigated the effects of a reduced RUTF dose on the daily energy and macronutrient intakes, the proportion of energy coming from CFF, and the mean probability of adequacy (MPA) of intake in 11 micronutrients of 516 children aged 6-59 mo who were treated for SAM in Burkina Faso. The data were collected using a single 24-h multipass dietary recall, 1 mo after starting treatment, from December 2016 to August 2018, repeated on a subsample of 66 children. Differences between children receiving the reduced RUTF (intervention arm) and those receiving standard RUTF (control arm) were assessed by linear mixed models. Daily energy intake was lower (P < 0.01) in the intervention arm (mean ± SD 1321 ± 339 kcal) than in the control arm (1467 ± 319 kcal). CFF contributed to 40% of the daily energy intake in the intervention and 35% in the control arm. The MPA for 11 micronutrients was 0.89 ± 0.1 in the intervention arm and 0.95 ± 0.07 in the control arm (P = 0.06). Reducing the dose of RUTF during SAM treatment had a negative impact on daily energy intake of the children. Despite this, children covered their recommended energy intake. The energy intake coming from CFF was similar between arms, suggesting that children's feeding practices did not change due to the reduction in RUTF in this context. This trial was registered at the IRSCTN registry as ISRCTN50039021
Keywords: Burkina Faso; children with severe acute malnutrition; complementary feeding; energy and micronutrient adequacy; ready-to-use therapeutic food